2016
DOI: 10.1128/aac.03074-15
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Complicated Intra-abdominal Infections Involving Pseudomonas aeruginosa from a Randomized, Double-Blind, Phase 3 Ceftolozane-Tazobactam Study

Abstract: c Ceftolozane-tazobactam is active against Gram-negative pathogens, including multidrug-resistant Pseudomonas aeruginosa. In a subgroup analysis of patients with complicated intra-abdominal infections (cIAIs) involving P. aeruginosa from a phase 3 program, ceftolozane-tazobactam demonstrated potent in vitro activity against P. aeruginosa. Clinical cure in the microbiologically evaluable population was 100% (26/26) for ceftolozane-tazobactam plus metronidazole and 93.1% (27/29) for meropenem. These findings sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…C/T was approved by the U.S. Food and Drug Administration in 2014 for the treatment of complicated intra-abdominal infections (cIAI, in combination with metronidazole) and complicated urinary tract infections (cUTI) (1). In clinical trials, C/T demonstrated noninferiority to meropenem when used in combination with metronidazole for the treatment of cIAIs (2,3). Additionally, C/T was noninferior to levofloxacin for the treatment of cUTIs, including pyelonephritis (4), which was mainly attributable to high rates of levofloxacin-resistant isolates among cUTI-causing bacteria (5,6).…”
mentioning
confidence: 99%
“…C/T was approved by the U.S. Food and Drug Administration in 2014 for the treatment of complicated intra-abdominal infections (cIAI, in combination with metronidazole) and complicated urinary tract infections (cUTI) (1). In clinical trials, C/T demonstrated noninferiority to meropenem when used in combination with metronidazole for the treatment of cIAIs (2,3). Additionally, C/T was noninferior to levofloxacin for the treatment of cUTIs, including pyelonephritis (4), which was mainly attributable to high rates of levofloxacin-resistant isolates among cUTI-causing bacteria (5,6).…”
mentioning
confidence: 99%
“…Lack of therapeutic options for the treatment of P. aeruginosa infections has been an increasing concern as antibiotic resistance continues to evolve. Specifically with regards to intraabdominal infections, resistance has led to the study and recent FDA approval of two new cephalosporin/β‐lactamase inhibitor combinations, ceftazidime‐avibactam and ceftolozane‐tazobactam . These agents initially represented advancements in the ability to treat organisms with few other therapeutic options secondary to antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically with regards to intraabdominal infections, resistance has led to the study and recent FDA approval of two new cephalosporin/ b-lactamase inhibitor combinations, ceftazidimeavibactam and ceftolozane-tazobactam. 10,11 These agents initially represented advancements in the ability to treat organisms with few other therapeutic options secondary to antimicrobial resistance. Despite the promise of these two newer agents for complicated intraabdominal infections caused by MDR gram-negative bacilli, resistance is being increasingly encountered.…”
Section: Discussionmentioning
confidence: 99%
“…In the study from Wagenlehner et al 6 on C/T and UTI, 23 PSA were involved but their antimicrobial susceptibilities are unknown. Miller et al 8 studied cIAI due to PSA; among them 26 MDR PSA were involved and treated by CT with a cure rate of 93%. Also, Castón et al 7 found that CT as salvage therapy for pneumonia due to MDR PSA was effective.…”
Section: Discussionmentioning
confidence: 99%